2012
DOI: 10.1093/icvts/ivs009
|View full text |Cite
|
Sign up to set email alerts
|

The effect of neoadjuvant chemoradiotherapy on airway colonization and postoperative respiratory complications in patients undergoing oesophagectomy for oesophageal cancer

Abstract: Respiratory complication is one of the important postoperative complications of oesophageal cancer. The aim of this study was to evaluate whether neoadjuvant chemotherapy before surgery is effective for postoperative respiratory complications. In this study, patients with oesophageal cancer were divided into two group: one with neoadjuvant therapy and the other without neoadjuvant therapy. Before surgery, they all underwent bronchoscopy and bronchoalveolar lavage. We evaluated respiratory complications and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 15 publications
(17 reference statements)
0
9
0
Order By: Relevance
“…). The sensitivity analysis performed by excluding trials conducted in the 1980s, the trial with a Jadad score of 1 or the trial that contained neither histopathology of the tumour nor information on the chemotherapy regimen showed a similar effect size to that in the analysis including all studies (data not shown). The histological subgroup analysis revealed no significant heterogeneity within subgroups and among subgroups.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…). The sensitivity analysis performed by excluding trials conducted in the 1980s, the trial with a Jadad score of 1 or the trial that contained neither histopathology of the tumour nor information on the chemotherapy regimen showed a similar effect size to that in the analysis including all studies (data not shown). The histological subgroup analysis revealed no significant heterogeneity within subgroups and among subgroups.…”
Section: Resultsmentioning
confidence: 92%
“…). Seven were randomized comparisons of neoadjuvant chemotherapy versus surgery alone, 11 were randomized comparisons of neoadjuvant chemoradiotherapy versus surgery alone, and two were randomized comparisons of neoadjuvant chemoradiotherapy versus neoadjuvant chemotherapy. A three‐arm study that compared neoadjuvant chemoradiotherapy versus adjuvant chemoradiotherapy versus surgery alone was treated as a two‐arm study that compared neoadjuvant chemoradiotherapy versus surgery alone.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…13 In a study of 40 patients by Bagheri et al, respiratory complications were closely analyzed, and although there was a significant correlation between the number of microorganisms in the sputum and difficulty in weaning, there was no correlation found between neoadjuvant treatment and pulmonary complications. 15 Several meta-analyses showed a decrease in mortality without any proof of a decrease in postoperative complications, but most trials failed to produce information about postoperative complications. 4 , 6 , 9 , 17 Greer et al found no difference in their meta-analysis and concluded that there was a need for large, randomized trials.…”
Section: Discussionmentioning
confidence: 99%
“…Perioperative risk factors associated with postoperative pulmonary infection include the existence of pulmonary inflammation and suboptimal control of infection before surgery for patients with chronic bronchitis, chronic cardiac insufficiency, age [≥80 years (5)], a long disease course, obesity (6), smoking (7), excessive drinking, diabetes, malnutrition (7), chronic obstructive pulmonary disease (COPD) (8), preoperative chemotherapy (9), intraoperative use of single lung ventilation, and large intraoperative blood loss (10). In order to reduce postoperative pulmonary complications during esophageal cancer surgery, protective strategies should include an accurate assessment of the patient's preoperative pulmonary function (11); a good understanding of the effect of applying respiratory irritant drugs during anesthesia and the effects of anesthesia on the respiratory tract; attention to reduce physical damage to lung tissue while using doublelumen tracheal intubation; and the application of active measures after surgery, such as, prophylactic antibiotics, pulmonary toilet and nutritional support.…”
mentioning
confidence: 99%